Evidences of a New Psychobiotic Formulation on Body Composition and Anxiety. (24th September 2017) - Colica, Carmela; Avolio, Ennio; Bollero, Patrizio; Costa de Miranda, Renata; Ferraro, Simona; Sinibaldi Salimei, Paola; De Lorenzo, Antonino; Di Renzo, Laura
Abstract : Background . Gut microbiota is implied in obesity, because of its ability to harvest energy from diet, and in the regulation of behavior. Given the link between gut microbiota, body composition, obesity, and anxiety, the aim of this study was to evaluate the effects of a new psychobiotic formulation. Methods . Eligible patients were randomly divided into three groups: psychobiotics oral suspension group (POSG); dietary treatment group (DTG); combined treatment group (CTG). All subjects underwent body composition and psychological profile evaluation. Results . Significant changes in body composition parameters in each group were relieved after all treatments. Hamilton anxiety rating scale (HAM-A) highlighted a significant reduction of the total score for all study population after treatments in POSG (p = 0.01 ) and CTG (p = 0.04 ). A reduction of HAM-A total score in anxious subjects in POSG or CTG and a significant reduction of positive subjects for HAM-A in POSG (p = 0.03 ) and in CDG (p = 0.01 ) were shown. Discussion . Three-week intake of selected POS represents a good approach to solve problems related to obesity and behavior disorders. However, new clinical trials need to be performed on a larger population and for a longer period of treatment before definitive conclusions can be made. This trial is registered with NCT01890070 .